PROCESSOR SCHEDULING TECHNIQUES IN COMPUTER OPERATING SYSTEM - Susi Arlita Anggraeni; Susi Wagiyati P, SKom, MM (Jurnal Sistem Informasi, 1999)
The main task of an operating system is to monitor and oversee all developmentactivities in the process of the operating system dynamically track the status of theprocess changes that occur in the system overall. All the activities that occurred in theoperating system, such occur in the processor in carrying out its activities, the needfor a rescheduling. Thus, by the implementation of all processes can be served fairly.The operating system is known, several techniques for scheduling. Differencesbetween each scheduling technique lies in the process of coming to the screening.And each has a characteristic penjaualan techniques, goals, and unique applications.